2011
DOI: 10.1021/la202509m
|View full text |Cite
|
Sign up to set email alerts
|

A General Approach to Controlling the Surface Composition of Poly(ethylene oxide)-Based Block Copolymers for Antifouling Coatings

Abstract: To control the surface properties of a polystyrene-block-poly(ethylene oxide) diblock copolymer, perfluorinated chemical moieties were specifically incorporated into the block copolymer backbone. A polystyrene-block-poly[(ethylene oxide)-stat-(allyl glycidyl ether)] [PS-b-P(EO-stat-AGE)] statistical diblock terpolymer was synthesized with varying incorporations of allyl glycidyl ether (AGE) in the poly(ethylene oxide) block from 0 to 17 mol %. The pendant alkenes of the AGE repeat units were subsequently funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 63 publications
3
102
0
Order By: Relevance
“…In fact, it has been shown that the allyl groups on PAGE backbone can be readily modified with biologically-relevant molecules of interest via thiol-ene radical coupling. 65 Based on these features, PAGE-based materials have recently been used for hydrogel formation, 66 nanopatterning biomolecules, 67 drug delivery, [68][69][70] and lithium batteries. 71 In our approach, PFS56-b-PAGE156 was first synthesized as an intermediate target.…”
Section: Synthesis and Characterization Of Amphiphilicmentioning
confidence: 99%
“…In fact, it has been shown that the allyl groups on PAGE backbone can be readily modified with biologically-relevant molecules of interest via thiol-ene radical coupling. 65 Based on these features, PAGE-based materials have recently been used for hydrogel formation, 66 nanopatterning biomolecules, 67 drug delivery, [68][69][70] and lithium batteries. 71 In our approach, PFS56-b-PAGE156 was first synthesized as an intermediate target.…”
Section: Synthesis and Characterization Of Amphiphilicmentioning
confidence: 99%
“…Cho et al 29 synthesized amphiphilic copolymers with side chains of hydrophilic PEO blocks and hydrophobic blocks of polystyrene (PS) and polyisoprene (PI) with clear decrease of the number of attached microalga and diatom cells as the PEO content of increased. A similar approach using ethoxylated fluoroalkyl side chains were previously used with success 30,31 . Copolymers with zwitterionic segments have been explored by other groups.…”
Section: Introductionmentioning
confidence: 99%
“…However, this technique requires intense tunable X-rays and for this reason must be performed at synchrotrons. [38][39][40] Arguably, one of the most influential analytical techniques in the polymer/water interface research field is the relatively new spectroscopic tool, sum frequency generation (SFG) vibrational spectroscopy. This technique allows researchers to study molecular vibrations in real time and in situ only where centrosymmetry is broken and therefore solely focuses on the water/polymer structured interface, unlike other techniques.…”
mentioning
confidence: 99%